Price competition or technology improvement? An investigation of green car technology. Issue 9 (3rd May 2021) - Kim, Byung Cho; Rhim, Hosun; Yang, Hongsuk
Abstract : Huge investments in green car research are being made in both the private and public sectors to cope with fuel shortage and environmental challenges. While the future of the green car industry is believed to be promising, its current status of technology is still remote from full-scale commercialisation. Interestingly, car manufacturers focus on different technologies for green car development, for instance, electric, fuel cells, and clean diesel. Given the platform characteristics of green car technology and the technology gap among manufacturers, an interesting question becomes whether both technologically superior and inferior green car manufacturers survive competition and if so, under what conditions. In this paper, we examine competing green car manufacturers' strategic choice between price competition and technology improvement (e.g. R&D investment). Grounded in a stylised model, we find the profit- and welfare-maximising price levels and examine technology improvement effort. Next, we investigate how the scope of network externality and cost differential influence manufacturers' strategic choices, and discuss the welfare implications.